Carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material and preparation method thereof

By using carbon fiber reinforced nylon 66/polyphenylene sulfide composite material, and utilizing plasma treatment and silane coupling agents to form a continuous bonding layer, the problem of insufficient high-temperature resistance and mechanical properties of existing materials at medium and high temperatures has been solved, enabling its application in automobiles and electronic devices.

CN121379137APending Publication Date: 2026-01-23SHANDONG ADVANCED MATERIALS RES INST CO LTD +2

Patent Information

Application Number
CN202511497305.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing carbon fiber reinforced nylon composites lack sufficient high-temperature resistance and mechanical properties at medium and high temperatures, making it difficult to meet the requirements of lightweighting in automobiles and miniaturization in electronic devices, and they also have high processing costs.

Method used

A carbon fiber reinforced nylon 66/polyphenylene sulfide composite material is used. Active groups are introduced into the surface of the carbon fiber by plasma treatment. Combined with silane coupling agent and maleic anhydride grafted polyphenylene sulfide, a continuous bonding layer is formed to realize a rigid-flexible interpenetrating network of nylon 66 and polyphenylene sulfide. Segmented pressure injection molding is used.

Benefits of technology

The material exhibits excellent high-temperature resistance and impact toughness at medium and high temperatures, making it suitable for automotive engine compartments and electronic high-voltage components. It also offers good processability and environmental resistance, meeting the comprehensive performance requirements of medium- and high-temperature structural components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121379137A_ABST
    Figure CN121379137A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer composite materials, in particular to a carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material and a preparation method thereof.The carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material is prepared from, by weight, 40-55 parts of nylon 66, 30-45 parts of polyphenylene sulfide, 15-30 parts of carbon fibers, 5-6 parts of compatilizer, 0.8-1.2 parts of antioxidant and 3-4 parts of flexibilizer, the flexibilizer is ethylene-octylene copolymer grafted maleic anhydride, the grafting rate is 1.2-1.5%, the flexibilizer is ethylene-octylene copolymer grafted maleic anhydride, the grafting rate is 0.8-1.0%, and the antioxidant is a mixture of an antioxidant 1010 and an antioxidant 168 according to a mass ratio of 1: 1. The composite material prepared by the invention is suitable for medium-high temperature scenes, not only solves the problems of insufficient high temperature resistance and poor mechanical properties of traditional materials, but also has good processability and environmental tolerance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of high polymer composite materials, and particularly relates to a carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material and a preparation method thereof. BACKGROUND

[0002] In recent years, with the increase in the production of carbon fibers and the reduction in the price of the carbon fibers, the carbon fiber reinforced thermoplastic resin composite material is applied more and more widely. For example, US patent US6231788 discloses a carbon fiber composite material with electromagnetic shielding property which is composed of a PC-ABS resin composite and carbon fibers, and can be used for dustproof equipment and notebook computer housings. Chinese patent CN101139462 discloses a flame-retardant carbon fiber composite material which is composed of a polyamide resin, carbon fibers, a red phosphorus flame retardant, a toughening agent and the like.

[0003] With the development requirements of the light weight of automobiles, the miniaturization of electronic equipment and the corrosion resistance of chemical equipment, higher requirements are put forward for the structural materials in terms of the high-temperature stability, high strength, light weight and environmental resistance. The current mainstream high polymer-based composite material has the following technical shortcomings and cannot meet the above requirements. For example, the carbon fiber reinforced nylon / PEEK composite material has excellent high-temperature resistance and mechanical properties, but the cost of the PEEK resin is extremely high, and the molding temperature needs to be 380-420 DEG C, which easily leads to the thermal oxidative degradation of nylon 66, and the defect rate of the finished product is high, so the carbon fiber reinforced nylon / PEEK composite material cannot adapt to the cost and processing requirements of industrial mass production. The carbon fiber reinforced nylon / polyformaldehyde composite material has excellent processability and low cost, but the polyformaldehyde has poor high-temperature resistance, and is easily decomposed to produce formaldehyde at a temperature above 120 DEG C, and has weak chemical corrosion resistance.

[0004] Therefore, there is an urgent need for a carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material and a preparation method thereof to solve the above problems. SUMMARY

[0005] To achieve the above object, the following technical scheme is adopted in the application. The carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material comprises, by weight, 40-55 parts of nylon 66, 30-45 parts of polyphenylene sulfide, 15-30 parts of carbon fibers, 5-6 parts of a compatilizer, 0.8-1.2 parts of an antioxidant and 3-4 parts of a toughening agent. The compatilizer is maleic anhydride grafted polyphenylene sulfide, and the grafting rate is 1.2-1.5%. The toughening agent is ethylene-octene copolymer grafted maleic anhydride, and the grafting rate is 0.8-1.0%. Further, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 at a mass ratio of 1:1.

[0006] The application further discloses a preparation method of the carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material. Step 100, raw material pretreatment, nylon 66 is vacuum dried at 120-130℃ for 4-6h, remove moisture to moisture content≤0.05%; polyphenylene sulfide is vacuum dried at 100-110℃ for 6-8h, remove moisture to moisture content≤0.02%; Step 200, carbon fiber pretreatment, carbon fiber is soaked in 2%-3% silane coupling agent KH550 ethanol solution, bath ratio is 1:20, stirring at 60-70℃ for 2-3h, then dried at 120℃ for 4h; Step 300, blending extrusion, pretreated nylon 66, polyphenylene sulfide, compatibilizer, antioxidant, toughening agent are added to the main feeding port of the twin screw extruder, carbon fiber is added through the side feeding port, finally the extruded strip is obtained; Step 400, water cooling and granulation, the extruded strip is cooled by circulating water at 20-30℃, and after the surface temperature of the extruded strip is cooled to≤40℃, it is fed into the granulator, and finally the composite particles are obtained; Step 500, injection processing, the composite particles are vacuum dried at 110-120℃ for 3-4h, then added to the hopper of the injection molding machine, and finally the carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material is obtained.

[0007] Further, in step 100, when treating polyphenylene sulfide, a stepwise temperature rising mode is adopted, first set at 80℃ for 2h, then increase the temperature.

[0008] Further, in step 200, the carbon fiber is first treated by plasma to introduce hydroxyl active groups on its surface.

[0009] Further, in step 300, the temperature of the first zone of the twin screw extruder is 260-270℃, the temperature of the second zone is 270-280℃, the temperature of the third zone is 280-290℃, the temperature of the fourth zone is 285-295℃, and the temperature of the die head is 290-300℃, and the screw rotation speed is 300-350r / min.

[0010] Further, in step 500, the temperature of the first zone of the barrel is 270-280℃, the temperature of the second zone is 280-290℃, the temperature of the third zone is 290-300℃, the temperature of the nozzle is 295-305℃, and the temperature of the mold is 120-140℃.

[0011] Further, in step 500, during injection, segmented pressure is used, the filling stage pressure is 100-120MPa, when the composite particles are filled to 90-95% of the cavity volume, it is converted to the holding stage, the pressure is 80-90MPa, and the holding time is 16-20s.

[0012] Compared with existing technologies, the technical solution of this application achieves a performance breakthrough through a three-level synergistic mechanism. A continuous bonding layer is constructed at the interface bonding level, avoiding delamination at medium and high temperatures. The blending of nylon 66 and polyphenylene sulfide forms a rigid-flexible interpenetrating network, balancing high-temperature resistance and impact toughness. This material is suitable for medium- and high-temperature applications such as automotive engine compartments and electronic high-voltage components. It solves the problems of insufficient high-temperature resistance and poor mechanical properties of traditional materials, while also possessing good processability and environmental tolerance. It can meet the comprehensive requirements of medium- and high-temperature structural components for performance, reliability, and practicality, filling a gap in existing technologies. Attached Figure Description

[0013] Appendix Figure 1 This is a process flow diagram of the preparation method of the present invention. Detailed Implementation

[0014] The present application will be further described in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this application, those skilled in the art can make various alterations or modifications to this application, and these equivalent forms also fall within the scope defined by this application.

[0015] A carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material, by weight, comprises 40-55 parts nylon 66, 30-45 parts polyphenylene sulfide, 15-30 parts carbon fiber, 5-6 parts compatibilizer, 0.8-1.2 parts antioxidant, and 3-4 parts toughening agent. The compatibilizer is maleic anhydride-grafted polyphenylene sulfide with a grafting rate of 1.2-1.5%. The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio. The toughening agent is an ethylene-octene copolymer grafted with maleic anhydride with a grafting rate of 0.8-1.0%.

[0016] As attached Figure 1 As shown, a method for preparing the above-mentioned carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material includes the following steps: Step 100, raw material pretreatment: First, nylon 66 granules are passed through an 80-mesh sieve to remove dust and agglomerated particles. Then, nylon 66 is vacuum dried at 120-130℃ for 4-6 hours to remove moisture until the moisture content is ≤0.05%. Polyphenylene sulfide is vacuum dried at 100-110℃ for 6-8 hours to remove moisture until the moisture content is ≤0.02% to avoid the generation of bubbles during subsequent molding. When processing polyphenylene sulfide, a stepped heating mode is adopted. First, the temperature is set at 80℃ and held for 2 hours, and then the temperature is increased to reduce the fluctuation of crystallinity of polyphenylene sulfide caused by rapid heating. Step 200, carbon fiber pretreatment, first, the carbon fiber is treated by plasma to introduce hydroxyl active groups on the surface to improve the grafting efficiency of the subsequent silane coupling agent, the carbon fiber is immersed in a silane coupling agent KH550 ethanol solution with a mass concentration of 2%-3%, the bath ratio is 1:20, stirring at 60-70℃ for 2-3h, and then drying at 120℃ for 4h to enhance the interfacial bonding strength of the carbon fiber and the resin matrix; The amino group of the silane coupling agent KH550 will undergo dehydration condensation reaction with the hydroxyl group on the surface of the carbon fiber to form a covalent bond -O-Si-O-, at the same time, the alkoxyl group of the silane coupling agent KH550 will undergo ring-opening reaction with the anhydride group of the compatibilizer to form a continuous interfacial layer of carbon fiber-coupling agent-compatibilizer-resin matrix, the interfacial bonding strength is improved, and the interfacial delamination at medium and high temperature can be avoided.

[0017] At the same time, the carbon fiber surface itself is relatively inert, and direct mixing with nylon 66 and polyphenylene sulfide can easily cause interfacial debonding. In this application, plasma treatment is used, which can break part of the C-C covalent bond on the surface of the carbon fiber by high-energy particle bombardment, introduce a large number of active groups such as hydroxyl and carboxyl groups, and at the same time, roughen the surface of the carbon fiber to increase the contact area with the resin, which can effectively provide anchoring sites for subsequent silane coupling agent grafting.

[0018] Step 300, blending extrusion, the pretreated nylon 66, polyphenylene sulfide, compatibilizer, antioxidant, and toughening agent are added to the main feeding port of the double screw extruder, and the carbon fiber is added through the side feeding port to avoid premature degradation of the carbon fiber at high temperature in the main feeding port, and finally the extruded strip is obtained, wherein the temperature of the first zone of the double screw extruder is 260-270℃, the temperature of the second zone is 270-280℃, the temperature of the third zone is 280-290℃, the temperature of the fourth zone is 285-295℃, and the temperature of the die head is 290-300℃, and the screw rotation speed is 300-350r / min; Step 400, water cooling and granulation, the extruded strip is cooled by circulating water at 20-30℃, in order to avoid stress caused by temperature difference, the water temperature fluctuation is ≤2℃, after the surface temperature of the extruded strip is cooled to ≤40℃, it is put into the granulator, and finally the composite particles are obtained; Step 500, injection molding treatment, the composite particles are vacuum dried at 110-120℃ for 3-4h, then added to the hopper of the injection molding machine, and finally the carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material is obtained. Among them, the temperature of the first zone of the barrel is 270-280℃, the temperature of the second zone is 280-290℃, the temperature of the third zone is 290-300℃, the temperature of the nozzle is 295-305℃, and the temperature of the mold is 120-140℃.

[0019] At the time of injection, segmented pressure is adopted, the filling stage pressure is 100-120 MPa, when the composite particles are filled to 90-95% of the cavity volume, the pressure is switched to the holding stage, the pressure is 80-90 MPa, the holding time is 16-20 s, if the filling pressure is too low or the speed is too slow, carbon fibers are prone to sedimentation when flowing in the cavity, resulting in uneven local fiber content, and finally affecting the consistency of the mechanical properties of the material. If the high pressure is maintained when the composite particles are filled to 90-95% of the cavity volume, the carbon fibers are prone to be broken by the shearing force under high pressure, and at the same time, the high pressure will cause the composite particle melt to be excessively compressed, resulting in a large internal stress in the cavity after cooling, and at the same time, the high pressure will also cause the composite particle melt to penetrate into the gap between the mold, forming a flash. By reducing the pressure to the holding stage of 80-90 MPa, the volume shrinkage caused by cooling can be supplemented by the appropriate pressure, and at the same time, the damage to the carbon fibers by the shearing force can be reduced, the internal stress and the probability of flash generation can be reduced, and finally the dimensional stability and mechanical properties of the composite material can be ensured.

[0020] The technical scheme of the present application realizes performance breakthrough through a three-stage synergistic mechanism, builds a continuous bonding layer from the aspect of interface bonding, avoids delamination at medium and high temperatures, and forms a rigid-flexible interpenetrating network through blending of nylon 66 and polyphenylene sulfide, thereby taking into account high-temperature resistance and impact toughness. The material can be adapted to medium and high temperature scenes such as automobile engine compartments and electronic high-voltage components, solves the problems of insufficient high-temperature resistance and poor mechanical properties of traditional materials, has good processability and environmental resistance, meets the comprehensive needs of performance, reliability and practicality of medium and high temperature structural parts, and fills the gap in the prior art.

[0021] Embodiment one A carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material, by weight, comprises 55 parts of nylon 66, 30 parts of polyphenylene sulfide, 15 parts of carbon fiber, 5 parts of a compatibilizer, 0.8 parts of an antioxidant, and 3 parts of a toughening agent. The compatibilizer is maleic anhydride grafted polyphenylene sulfide with a grafting rate of 1.2%. The toughening agent is ethylene-octene copolymer grafted maleic anhydride with a grafting rate of 0.8%.

[0022] A preparation method for preparing the above-mentioned carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material, comprising the following steps: Step 100, raw material pretreatment, first, the nylon 66 particles are passed through an 80-mesh sieve to remove dust and agglomerated particles, then the nylon 66 is vacuum dried at 120°C for 6h to remove water to a water content of 0.04%; the polyphenylene sulfide is vacuum dried at 100°C for 8h to remove water to a water content of 0.02%; Step 200, carbon fiber pretreatment, first carbon fiber is treated by plasma, hydroxyl active groups are introduced on the surface of the carbon fiber, then the carbon fiber is soaked in a 2% by mass concentration silane coupling agent KH550 ethanol solution, stirred at 60℃ for 3h, and then dried at 120℃ for 4h; Step 300, blending extrusion, the pretreated nylon 66, polyphenylene sulfide, compatibilizer, antioxidant, toughening agent, and carbon fiber are added into a twin-screw extruder, and finally an extruded strip is obtained, wherein the temperature of the first zone of the twin-screw extruder is 260℃, the temperature of the second zone is 270℃, the temperature of the third zone is 280℃, the temperature of the fourth zone is 285℃, the temperature of the die head is 290℃, and the screw rotation speed is 300r / min; Step 400, water cooling and granulation, the extruded strip is cooled by circulating water at 20℃, and after the surface temperature of the extruded strip is cooled to 38℃, it is fed into a granulator, and finally composite particles are obtained; Step 500, injection molding treatment, the composite particles are vacuum dried at 110℃ for 4h, then added into the hopper of an injection molding machine, and finally a carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material is obtained. Among them, the temperature of the first zone of the barrel is 270℃, the temperature of the second zone is 280℃, the temperature of the third zone is 290℃, the temperature of the nozzle is 295℃, and the temperature of the mold is 120℃.

[0023] During injection, segmented pressure is used, the filling stage pressure is 100MPa, when the composite particles are filled to 90% of the cavity volume, it is switched to the holding stage, the pressure is 80MPa, and the holding time is 16s.

[0024] Through testing, the medium-high temperature stability is that the tensile strength retention rate reaches 85% after 1000h of long-term use at 160℃, the heat distortion temperature is 225℃, meeting the medium temperature use requirements of electronic low pressure parts, and the mechanical properties are that the tensile strength is 352MPa, the flexural modulus is 25.3GPa, and the notched impact strength reaches 11.5kJ / m 2 , the toughness advantage is significant, and it is suitable for low load and high toughness requirement medium temperature scenes.

[0025] Example Two A carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material, by weight, includes 50 parts of nylon 66, 35 parts of polyphenylene sulfide, 25 parts of carbon fiber, 6 parts of compatibilizer, 1 part of antioxidant, and 4 parts of toughening agent, wherein the compatibilizer is maleic anhydride grafted polyphenylene sulfide with a grafting rate of 1.4%, and the toughening agent is ethylene-octene copolymer grafted maleic anhydride with a grafting rate of 0.9%.

[0026] A preparation method for preparing the above-mentioned carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material, comprising the following steps: Step 100, raw material pretreatment, first pass nylon 66 particles through 80 mesh sieve, then vacuum dry nylon 66 at 125℃ for 5h, remove moisture to moisture content 0.03%; polyphenylene sulfide is vacuum dried at 105℃ for 7h, remove moisture to moisture content 0.015%; Step 200, carbon fiber pretreatment, first use plasma treatment on carbon fiber, then soak carbon fiber in 2.5% silane coupling agent KH550 ethanol solution, stir at 65℃ for 2.5h, then dry at 120℃ for 4h; Step 300, blending extrusion, add pretreated nylon 66, polyphenylene sulfide, compatibilizer, antioxidant, toughening agent, carbon fiber into double screw extruder, finally get extruded strip, wherein the temperature of one zone of double screw extruder is 265℃, the temperature of two zone is 275℃, the temperature of three zone is 285℃, the temperature of four zone is 290℃, the temperature of head is 295℃, the screw speed is 320r / min; Step 400, water cooling and granulation, cool extruded strip through 25℃ circulating water, after cooling to 35℃ of extruded strip surface temperature, enter the granulator, finally get composite particles; Step 500, injection processing, vacuum dry composite particles at 115℃ for 3.5h, then add into injection machine hopper, finally get carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material. Wherein, the temperature of one zone of cylinder is 275℃, the temperature of two zone is 285℃, the temperature of three zone is 295℃, the temperature of nozzle is 300℃, the temperature of mold is 130℃.

[0027] During injection, use segmented pressure, the pressure in filling stage is 110MPa, when composite particles fill to 93% of cavity volume, change to pressure maintaining stage, the pressure is 85MPa, the pressure maintaining time is 18s.

[0028] After testing, in medium and high temperature stability, the tensile strength retention rate reaches 90% after 1000h long-term use at 175℃, the heat distortion temperature is 238℃, the tensile strength is 378MPa, the flexural modulus is 28.6GPa, the notched impact strength is 11.8kJ / m 2 , which can resist engine vibration impact and accurately match the comprehensive needs of medium and high temperature high load scenes.

[0029] Example three A kind of carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material, by weight, including 40 parts of nylon 66, 45 parts of polyphenylene sulfide, 30 parts of carbon fiber, 6 parts of compatibilizer, 1.2 parts of antioxidant, 4 parts of toughening agent, wherein the compatibilizer is maleic anhydride grafted polyphenylene sulfide, the grafting rate is 1.5%. The toughening agent is ethylene-octene copolymer grafted maleic anhydride, the grafting rate is 1.0%.

[0030] A preparation method for preparing the carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material, comprising the following steps: Step 100, raw material pretreatment, first pass the nylon 66 particles through an 80 mesh sieve, then vacuum dry the nylon 66 at 130℃ for 4h to remove moisture to a moisture content of 0.05%; vacuum dry the polyphenylene sulfide at 110℃ for 6h to remove moisture to a moisture content of 0.01%; Step 200, carbon fiber pretreatment, first treat the carbon fiber with plasma, then soak the carbon fiber in a 3% mass concentration silane coupling agent KH550 ethanol solution, stir at 60-70℃ for 2h, then dry at 120℃ for 4h; Step 300, blending extrusion, add the pretreated nylon 66, polyphenylene sulfide, compatibilizer, antioxidant, toughening agent, and carbon fiber into a twin-screw extruder, finally obtain an extruded strip, wherein the temperature of the first zone of the twin-screw extruder is 270℃, the temperature of the second zone is 280℃, the temperature of the third zone is 290℃, the temperature of the fourth zone is 295℃, the temperature of the die head is 300℃, and the screw rotation speed is 350r / min; Step 400, water cooling and granulation, cool the extruded strip in a 30℃ circulating water, after cooling to a surface temperature of the extruded strip of 40℃, enter a granulator, finally obtain composite particles; Step 500, injection molding treatment, vacuum dry the composite particles at 120℃ for 3h, then add them into the hopper of an injection molding machine, finally obtain the carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material. Among them, the temperature of the first zone of the barrel is 280℃, the temperature of the second zone is 290℃, the temperature of the third zone is 300℃, the temperature of the nozzle is 305℃, and the temperature of the mold is 140℃.

[0031] During injection, segmented pressure is used, the filling stage pressure is 120MPa, when the composite particles are filled to 95% of the cavity volume, it is switched to the holding stage, the pressure is 90MPa, and the holding time is 20s.

[0032] Through testing, in terms of medium-high temperature stability, the tensile strength retention rate reaches 88% after 1000h of long-term use at 180℃, the heat distortion temperature is 245℃, in terms of mechanical properties, the tensile strength is 395MPa, and the flexural modulus is 31.2GPa, which can replace part of the aluminum alloy to bear high load, and is suitable for high load and extreme medium temperature scenes.

[0033] Finally, it should be noted that: the above examples are only used to illustrate the technical solutions of the present application, but not to limit them; although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that: it can still modify the technical solutions recorded in the foregoing examples, or make equivalent replacement for part of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material, characterized in that: By weight, it includes 40-55 parts nylon 66, 30-45 parts polyphenylene sulfide, 15-30 parts carbon fiber, 5-6 parts compatibilizer, 0.8-1.2 parts antioxidant, and 3-4 parts toughening agent. The compatibilizer is maleic anhydride-grafted polyphenylene sulfide with a grafting rate of 1.2-1.5%, and the toughening agent is ethylene-octene copolymer-grafted maleic anhydride with a grafting rate of 0.8-1.0%.

2. The carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material according to claim 1, characterized in that: The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:

1.

3. A method for preparing carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material according to any one of claims 1-2, characterized in that: Includes the following steps: Step 100: Raw material pretreatment. Nylon 66 is vacuum dried at 120-130℃ for 4-6 hours to remove moisture until the moisture content is ≤0.05%. Polyphenylene sulfide is vacuum dried at 100-110℃ for 6-8 hours to remove moisture until the moisture content is ≤0.02%. Step 200, carbon fiber pretreatment: Immerse the carbon fiber in a 2%-3% (w / w) ethanol solution of silane coupling agent KH550, with a bath ratio of 1:20, stir at 60-70℃ for 2-3 hours, and then dry at 120℃ for 4 hours. Step 300, blending and extrusion: pretreated nylon 66, polyphenylene sulfide, compatibilizer, antioxidant and toughening agent are added to the main feed port of the twin-screw extruder, and carbon fiber is added through the side feed port to finally obtain the extruded strip; Step 400, water-cooled pelletizing: the extruded strip is cooled by circulating water at 20-30℃ until the surface temperature of the extruded strip is ≤40℃ before entering the pelletizer to finally obtain composite particles; Step 500: Injection molding process. The composite particles are vacuum dried at 110-120℃ for 3-4 hours and then added to the injection molding machine hopper to finally obtain carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material.

4. The method for preparing carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material according to claim 3, characterized in that: In step 100, when processing polyphenylene sulfide, a stepped heating mode is adopted. First, the temperature is set at 80℃ and held for 2 hours, and then the temperature is increased.

5. The method for preparing carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material according to claim 3, characterized in that: In step 200, the carbon fiber is first treated with plasma to introduce hydroxyl active groups on its surface.

6. The method for preparing carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material according to claim 3, characterized in that: In step 300, the temperature of the twin-screw extruder is 260-270℃ in zone 1, 270-280℃ in zone 2, 280-290℃ in zone 3, 285-295℃ in zone 4, 290-300℃ in the die head, and the screw speed is 300-350 r / min.

7. The method for preparing carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material according to claim 3, characterized in that: In step 500, the temperature of zone 1 of the barrel is 270-280℃, the temperature of zone 2 is 280-290℃, the temperature of zone 3 is 290-300℃, the nozzle temperature is 295-305℃, and the mold temperature is 120-140℃.

8. The method for preparing carbon fiber reinforced nylon 66 / polyphenylene sulfide composite material according to claim 3, characterized in that: In step 500, during injection, segmented pressure is used. The filling stage pressure is 100-120 MPa. When the composite particles fill 90-95% of the cavity volume, the pressure is switched to the holding stage, with a pressure of 80-90 MPa and a holding time of 16-20 seconds.

Citation Information

Patent Citations

  • Carbon-reinforced PC-ABS composition and articles made from same

    US6231788B1

Cited By

  • A fiber-reinforced polyphenylene sulfide / polyamide composite material, its preparation method and preparation system

    CN122302330A

  • A fiber-reinforced polyphenylene sulfide / polyamide composite, a method of making and a system for making

    CN122302330B